Estudo comparativo do uso de meloxicam por via intra-articular e sistêmica no controle da osteoartrite experimentalmente induzida em joelho de coelhos - Vidotto, Valéria Trombini (2013)
Objective: This study aimed to evaluate morphologic changes, as well as chondroprotective and intra-articular effects of meloxicam on joint repair in rabbits induced by experimental trochleoplasty, minimizing possible adverse side effects. Methods: Thirty-five rabbits were divided into four groups: the control group, which did not undergo surgery, and operated groups, which used different ways of administering the anti-inflammatory agent: systemic, 0.2 mg/kg; intra-articular, 0.5 mg/kg; positive group control, without meloxicam. Each operated group was divided according to the periods of 7 or 30 days evaluation after surgery. Results: Regarding macroscopic and histological evaluation of cartilage, after 30 days, most animals showed almost complete joint repair, the presence of few or no inflammatory cells; whereas part of the animals treated with meloxicam presented necrosis in the trochlear ridge and absence of inflammatory cells after 7 days. In positive control group, it was observed moderate inflammation and connective tissue proliferation. None of the animals in the operated groups showed irregularities 30 days after surgery. Conclusion: Either intra-articular or systemic, meloxicam revealed to be favorable to be used for joint repair and control of inflammatory reaction. © 2013 Sociedade Brasileira de Ortopedia e Traumatologia.